1979
DOI: 10.1152/jappl.1979.47.6.1251
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of contracted airway smooth muscle

Abstract: How does smooth muscle tone affect the properties of airways during breathing maneuvers? We have studied the dynamic relationships of airway pressure and cross-sectional area in excised dog lobes and isolated tracheal segments during simulated breathing maneuvers. When contracted by carbachol, airways developed complex hysteretic behavior, becoming less compliant in small tidal breaths and rapid deflations, and grossly hysteretic in large tidal maneuvers. For a given sequence of maneuvers the patterns of hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 0 publications
4
63
0
Order By: Relevance
“…FREDBERG et al [52] noted that the increase of muscle hysteresis referred to by LIM and co-workers [40,41] and SASAKI and HOPPIN [56] and upon which their argument hinges, happens if, and only if, the muscle is activated and subject to large ongoing tidal stretches; the opposite response occurs to smaller tidal stretches. That is, the hysteresis decreases and does so rather dramatically.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…FREDBERG et al [52] noted that the increase of muscle hysteresis referred to by LIM and co-workers [40,41] and SASAKI and HOPPIN [56] and upon which their argument hinges, happens if, and only if, the muscle is activated and subject to large ongoing tidal stretches; the opposite response occurs to smaller tidal stretches. That is, the hysteresis decreases and does so rather dramatically.…”
Section: Evidence Of Asm Involvement In Asthmamentioning
confidence: 99%
“…Response of activated ASM to oscillatory stress or strain As discussed briefly above, it has been known for a long time that length or force oscillations at physiologically relevant frequencies and amplitudes applied to activated ASM result in a reduction in the ability of the muscle to contract [22,23,45,56,58,[160][161][162][163][164]. Evidence that tidal volume oscillations had similar effects on airway calibre and Raw in experimental animals in vivo led WARNER et al [24], TEPPER et al [25] and SHEN et al [160] to suggest that the oscillation of the airways that occurs during tidal breathing might be a physiologically important mechanism for decreasing airway responsiveness.…”
Section: In Vitro Behaviour Of Asmmentioning
confidence: 99%
“…With the bronchi and lobe at the same dimensions, this contracted-relaxed Pbr difference could not have been due to primary changes in the lung parenchymal recoils of the passive elements, but could have resulted from force in the contracted smooth muscle. The pressure difference then represented the inward-acting force due to smooth muscle contraction and was designated as Psm (Sasaki and Hoppin 1979).…”
Section: Methodsmentioning
confidence: 99%
“…Our approach was principally similar to the study by Sasaki and Hoppin (1979). They studied airway smooth muscle force during carbachol-induced constriction in the excised dog lungs.…”
mentioning
confidence: 99%
“…airway mechanics ; airway smooth muscle ; isotonic contraction ; vagal stimulation Constriction of airway smooth muscle controls total and local ventilation by changing airway resistances. During dynamic respiratory maneuvers, the time course of airway caliber is determined by the balance of timing of passively length-cycled airway smooth muscle and shortening velocity of the contracted airway smooth muscle (Sasaki and Hoppin 1979). Stephens et al (1969) and Antonissen et al (1979) studied the shortening velocity of airway smooth muscle using excised trachealis muscle strips under electrical field stimulation and found that the force-velocity relationship was hyperbolic and could be described by Hill's equation (Hill 1938).…”
mentioning
confidence: 99%